A RATional choice for translational research? - Tim Aitman; Paraminder Dhillon; Aron M. Geurts (The Company of Biologists, 2016)
Future prospects continue to be strong for research using the rat as a model organism. New technology has enabled the proliferation of many new transgenic and knockout rat strains, the genomes of more than 40 rat strains have been sequenced, publications using the rat as a model continue to be produced at a steady rate, and discoveries of disease-associated genes and mechanisms from rat experiments abound, frequently with conservation of function between rats and humans. However, advances in genome technology have led to increasing insights into human disease directly from human genetic studies, pulling more and more researchers into the human genetics arena and placing funding for model organisms and their databases under threat. This, therefore, is a pivotal time for rat-based biomedical research - a timely moment to review progress and prospects - providing the inspiration for a new Special Collection focused on the impact of the model on translational science, launched in this issue of Disease Models & Mechanisms. What disease areas are most appropriate for research using rats? Why should the rat be favoured over other model organisms, and should the present levels of funding be continued? Which approaches should we expect to yield biologically and medically useful insights in the coming years? These are key issues that are addressed in the original Research Articles and reviews published in this Special Collection, and in this introductory Editorial. These exemplar articles serve as a landmark for the present status quo after a decade of major advances using the rat model and could help to guide the direction of rat research in the coming decade.